Bossing Design for the Wing Screws of the New Design Polar Icebreaker (M-13 Hull). - Hinterthan, Werner B. (1968)
The scope of this study includes alternate means of propulsion devices, selection of power distribution between the three shafts, positioning of the propellers, propeller blade tip clearances, shaft skew and rake and basic studies of the bossing design. Special considerations were given to the fairing of the wing bossing at the bossing-hull intersection and to the flow entering the center propeller. Other aspects are considered, such as the influence of ice-hull interaction, in so far as the state of the art permits. (Author)